Putting the environmental impact assessment process into practice for woodland caribou in the Alberta Oil Sands Region - Bentham, Paula R. (Rangifer, 2005)
Since 1985, woodland caribou (Rangifer tarandus caribou) have been designated as a threatened species in Alberta. Populations studied since the 1970s have been stable or declining, with no population increases documented. Resource expansion into previously undeveloped areas and associated increases in access have been implicated as possible causes for the declines. To facilitate development on caribou ranges, while ensuring the integrity and supply of caribou habitat, standing committees have been formed. The primary role of the committees is to act as advisory bodies to the government and to search for effective and efficient industrial operating guidelines. Recent research has been conducted on the responses of woodland caribou ecotypes to increased human and predator access. Based on this research, operating guidelines have been refined and implemented through Caribou Protection Plans. I discuss how the current operating guidelines are put into practice and linked to the Environmental Assessment process within the Oil Sands Region of Alberta. In particular, I discuss the origination of impact predictions, specific mitigation measures to reduce impacts and monitoring.
Keywords: Caribou Protection Plans; Environmental Impact Assessment; mitigation; monitoring; oil sands; operating guidelines; Rangifer tarandus caribou